The Enhancement of Start Up Business Competencies For Indonesian Migrant Workers In Korea - Nuraini Purwandari; Ruswiati Suryasaputra; Boy Firmansyah; Rr. Aryanti Kristantini (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Along with power departed work _ to many abroad _ frequent problems _ happens to workers Indonesian migrants , one of them about competence work you have every candidate worker Indonesian migrants . Beside enhancement competence through studies carry on worker Indonesian migrants can also provide himself with Skills technical certain in accordance their respective interests are like establish startup business , agriculture integrated nor form activity productive others . In Indonesia itself Lots perpetrator business with sufficient development _ good at first profession as worker migrants and one of them cooperate with Institute Business and Informatics Kosgoro 1957. Therefore That held activity Devotion To the Community by Institute Lecturers Business and Informatics Kosgoro 1957 collaborated with President of Kaya University and Busan University in Korea as well Embassy of the Republic of Indonesia in Korea. Purpose of activity This is give solution based on study academic on needs , challenges or problems faced _ Worker Migrants in South Korea. Besides that, it also helps finish problem related start digital business and opportunities investment productive others . Devotion method to this Society consists from counseling and discussion through offline and online seminar activities via zoom meeting application . The success of this community activity program showed with liveliness all participants and enthusiastic participant do discussion and questions answer with source .